Seismic Behaviour of Hybrid Precast Shear Walls with Partially Connected Vertically Distributed Reinforcements - Henglin Lv; Yuanzhou Wu; Xiongshi Hu; Cancan Huang; Kefang Liu (Advances in Civil Engineering)
This paper presents a joint mode for a vertical grouting sleeve and a partially distributed reinforced composite connection. The seismic performance of four hybrids precast shear walls with a shear span ratio of 1.83, an axial compression ratio of 0.20, and partially connected vertically distributed rebar was studied by pseudo-static tests. The connection ratios of the reinforced concrete with a vertical distribution were 100%, 67%, 50%, and 33% and were compared with cast-in-place shear walls. It was found that both the precast and cast-in-place specimens demonstrated bending and shear failure modes. Both ends of the mortar layer were cracked under compression, and steel connection failure occurred under the ultimate load. The load-displacement hysteresis curve was bow-shaped and relatively full; the yield load increased from 11.4 to 16.6, and the peak load increased from 4.2 to 6.8 compared with those of the cast-in-situ specimen. The strength degradation performance of the precast specimen was slightly weaker than that of the cast-in-place specimen. The ductility coefficient of the precast specimens was approximately 4, and the ultimate displacement angle was between 1/30 and 1/32, which was larger than the limit value of elastic-plastic interlayer displacement of shear wall structures required by the code. The reduction in the number of vertically distributed rebar connections led to a decrease in the bearing capacity, stiffness, ductility, and energy dissipation, but the impact was very small.